Interactions Between Intestinal Microbiota and Neural Mitochondria: A New Perspective on Communicating Pathway From Gut to Brain - Zhu, Yao; Li, Ying; Zhang, Qiang; Song, Yuanjian; Wang, Liang; Zhu, Zuobin (Frontiers in Microbiology, 2022)
Many studies shown that neurological diseases are associated with neural mitochondrial dysfunctions and microbiome composition alterations. Since mitochondria emerged from bacterial ancestors during endosymbiosis, mitochondria and bacteria had analogous genomic characteristics, similar bioactive compounds and comparable energy metabolism pathways. Therefore, it is necessary to rationalize the interactions of intestinal microbiota with neural mitochondria. Recent studies have identified neural mitochondrial dysfunction as a critical pathogenic factor for the onset and progress of multiple neurological disorders, in which the nonnegligible role of altered gut flora composition was increasingly noticed. Here, we proposed a new perspective of intestinal microbiota - neural mitochondria interaction as a communicating channel from gut to brain, which could help to extend the vision of gut-brain axis regulation and provide additional research directions on treatment and prevention of responsive neurological disorders.